Trade and Credit Reallocation: How Banks Help Shape Comparative Advantage - Christian Keuschnigg; Michael Kogler (Center for Economic Studies and ifo Institute (CESifo), 2018)
Trade and innovation cause structural change. Productive factors must flow from declining to growing industries. Banks play a major role in cutting credit to non-viable firms in downsizing sectors and in providing new credit to finance investment in expanding, innovative sectors. Structural parameters of a country's banking system thus influence comparative advantage and trade, and can magnify the gains from trade liberalization. The analysis shows how insolvency laws, minimum capital standards, and cost of bank equity determine credit reallocation, sectoral expansion and trade patterns.
Keywords: F10; G21; G28; 330; capital reallocation; banking; trade; comparative advantage